Effects of an Obesity Prevention Intervention on Physical Activity Among Preschool Children: The CHILE Study - Cruz, Theresa H. (Health Promot Pract, 2016)
BACKGROUND: Limited research addresses interventions to increase physical activity among American Indian and Hispanic preschool-aged children living in rural areas. We examined the impact of a Head Start-based intervention (Child Health Initiative for Lifelong Eating and Exercise [CHILE]) on physical activity at home. METHOD: Sixteen Head Start centers in predominantly Hispanic or American Indian communities were group randomized to the six-component intervention or a comparison group for 2 years. Structured surveys were administered at four assessment times to a convenience sample of caregivers of 655 children in the study. Multilevel modeling was used to assess the effects of the intervention on physical activity. RESULTS: The relative change in physical activity in the intervention group compared with the comparison group over the 2-year period was 1.56 (95% confidence interval [1.02, 2.38]; p = .04). Among specific promoted activities (ball playing, dancing, active games, jumping, and walking), dancing increased significantly in the intervention compared with the comparison group (2.9; 95% confidence interval [1.2, 7.1]; p = .02). CONCLUSIONS: The CHILE intervention was effective at increasing physical activity at home in preschool children in priority populations. Future research should focus on increasing family involvement and strengthening messaging about physical activity in these populations.